2021
DOI: 10.1017/s0967199421000265
|View full text |Cite
|
Sign up to set email alerts
|

Folliculogenesis-related genes are differently expressed in secondary and tertiary ovarian follicles

Abstract: Summary The relative mRNA abundance of 10 genes associated with folliculogenesis was compared between late preantral (secondary) and early antral (tertiary) ovarian follicles in goats. In total, 100 follicles in each category were mechanically isolated. The relative transcript abundance of the mRNAs were determined by qPCR. Data were analyzed using unpaired Student’s t-test. Of the 10 tested genes, ABLIM mRNA was not detected in either follicle category, six genes (SLIT3, TYMS, GTPBP1, AKR1C4, PIK3R6, and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In the ovary, elevated concentrations of progesterone or estradiol lead to enhanced CYTL1 expression; in the uterus, CYTL1 expression is significantly enhanced in endometrial cells with increasing concentrations of progesterone and estrogen, suggesting that CYTL1 is a candidate marker of endometrial tolerance and that upregulation of CYTL1 leads to significant proliferation of endometrial cells ( Ai et al, 2016 ). In addition, it has been reported that CYTL1 can mediate the regulation of different stages of folliculogenesis ( Moura et al, 2021 ). The tolerance of the endometrium is important for the reproduction of offspring in females, in the study, we hypothesized that the high expression of this gene during the PP contributes to ovarian maintenance and has an important role in egg production.…”
Section: Discussionmentioning
confidence: 99%
“…In the ovary, elevated concentrations of progesterone or estradiol lead to enhanced CYTL1 expression; in the uterus, CYTL1 expression is significantly enhanced in endometrial cells with increasing concentrations of progesterone and estrogen, suggesting that CYTL1 is a candidate marker of endometrial tolerance and that upregulation of CYTL1 leads to significant proliferation of endometrial cells ( Ai et al, 2016 ). In addition, it has been reported that CYTL1 can mediate the regulation of different stages of folliculogenesis ( Moura et al, 2021 ). The tolerance of the endometrium is important for the reproduction of offspring in females, in the study, we hypothesized that the high expression of this gene during the PP contributes to ovarian maintenance and has an important role in egg production.…”
Section: Discussionmentioning
confidence: 99%
“…The relaxation of selection was demonstrated with CST3, DNAJB4, DSG2, MRTO4, MFSD14A, NOSTRIN, PSPC1, and VWA8, which were potentially involved in various aspects of spermatogenesis [53,[79][80][81][82][83][84][85]; ITGB5, which played a role in male fertility [86][87][88]; IPO13, which was involved in meiosis of germ cells [89]; and GTPBP1, MRPS5, and PSPC1, which were involved in oogenesis [90][91][92]. CST3 regulated proteolysis in the male reproductive system [93], NOSTRIN was involved in placenta development [94], CA4 and ITM2B were differentially expressed in female and male reproductive tissues [95][96][97][98].…”
Section: Molecular Mechanisms Underlying Speciation Between Cryptic S...mentioning
confidence: 99%